Physical, mental and social consequences in civilians who have experienced war-related sexual violence: a systematic review (1981–2014) - Ba, I.; Bhopal, R.S. (Public health (London), 2017)
To identify the health outcomes of sexual violence on civilians in conflict zones between 1981 and 2014. Systematic review. For the purpose of this study, we defined sexual violence as sexual torture including, individual rape, gang rape, and sexual slavery. All types of conflicts were included (intrastate, interstate, and internationalized intrastate). Quantitative and mixed-method studies, reporting any physical, mental, and social consequences, were retrieved from Medline, Embase, Global Health, Global Health Library, WHOLIS, Popline, and Web of Sciences (n = 3075) and from checking reference lists and personal communications (n = 359). Data were analyzed using Microsoft Excel and MetaXL. Given inherent variation, the means derived from combining studies were misleading; thus, we focused on the range of values. The 20 studies were from six countries, five in Africa (18 studies), and especially in Democratic Republic of Congo (12 studies). The number of subjects varied from 63 to 20,517, with 17 studies including more than 100 subjects. Eight studies included males. Gang rape, rape, and abduction were the most commonly reported types of sexual violence. Sixteen studies provided data on physical outcomes of which the most common were pregnancy (range 3.4–46.3%), traumatic genital injuries/tears (range 2.1–28.7%), rectal and vaginal fistulae (range 9.0–40.7%), sexual problems/dysfunction (range 20.1–56.7%), and sexually transmitted diseases (range 4.6–83.6%). Mental health outcomes were reported in 14 studies, the most frequent being post-traumatic stress disorder (range 3.1–75.9%), anxiety (range 6.9–75%), and depression (range 8.8–76.5%). Eleven studies provided social outcomes, the most common being rejection by family and/or community (range of 3.5–28.5%) and spousal abandonment (range 6.1–64.7%). Wartime sexual violence is highly traumatic, causing multiple, long-term negative outcomes. The number and quality of studies published does not match the significance of the problem. The findings highlight the need for care of the survivors and their relatives and raise concerns about how they and their children will be affected in the long term. •First systematic review on the health consequences of war-related sexual violence on civilians.•Twenty studies were found, with research mainly in Africa. Rapes and gang rapes are salient features with female and male victims.•Common physical outcomes included pregnancy, traumatic genital injuries, fistulae, sexual dysfunction and STDs.•Mental outcomes included PTSD, anxiety, and depression; while the main social outcomes were rejection and spousal abandonment.•There is limited precise, valid, systematic data documenting the scope, frequency and consequences of war-related sexual violence.